Epinephrine and short-term survival in cardiogenic shock: an individual data meta-analysis of 2583 patients - Léopold, Valentine; Gayat, Etienne; Pirracchio, Romain; Spinar, Jindrich; Parenica, Jiri; Tarvasmäki, Tuukka; Lassus, Johan; Harjola, Veli-Pekka; Champion, Sébastien; Zannad, Faiez; Valente, Serafina; Urban, Philip; et al. (Intensive care medicine, 2018)
OBJECTIVE: Catecholamines have been the mainstay of pharmacological treatment of cardiogenic shock (CS). Recently, use of epinephrine has been associated with detrimental outcomes. In the present study we aimed to evaluate the association between epinephrine use and short-term mortality in all-cause CS patients. DESIGN: We performed a meta-analysis of individual data with prespecified inclusion criteria: (1) patients in non-surgical CS treated with inotropes and/or vasopressors and (2) at least 15% of patients treated with epinephrine administrated alone or in association with other inotropes/vasopressors. The primary outcome was short-term mortality. MEASUREMENTS AND RESULTS: Fourteen published cohorts and two unpublished data sets were included. We studied 2583 patients. Across all cohorts of patients, the incidence of epinephrine use was 37% (17-76%) and short-term mortality rate was 49% (21-69%). A positive correlation was found between percentages of epinephrine use and short-term mortality in the CS cohort. The risk of death was higher in epinephrine-treated CS patients (OR [CI] = 3.3 [2.8-3.9]) compared to patients treated with other drug regimens. Adjusted mortality risk remained striking in epinephrine-treated patients (n = 1227) (adjusted OR = 4.7 [3.4-6.4]). After propensity score matching, two sets of 338 matched patients were identified and epinephrine use remained associated with a strong detrimental impact on short-term mortality (OR = 4.2 [3.0-6.0]). CONCLUSIONS: In this very large cohort, epinephrine use for hemodynamic management of CS patients is associated with a threefold increase of risk of death.
Keywords: Male; Adult; Aged; dospělí; mužské pohlaví; senioři; kardiogenní šok; Shock, Cardiogenic; Propensity Score; tendenční skóre; adrenalin; Epinephrine; senioři nad 80 let; lidé; ženské pohlaví; Humans; Meta-analysis; Cardiogenic shock; Aged, 80 and over; Prognosis; koronární angioplastika; vazokonstriktory; Vasoconstrictor Agents; Female; lidé středního věku; Percutaneous Coronary Intervention; Middle Aged